Comparison of the Nutritional, Physicochemical, Technological–Functional, and Structural Properties and Antioxidant Compounds of Corn Kernel Flours from Native Mexican Maize Cultivated in Jalisco Highlands - Luis Alfonso Hernández-Villaseñor; Salvador Hernández-Estrada; Víctor Manuel Gómez-Rodríguez; Humberto Ramírez-Vega; Zuamí Villagrán; Araceli Ortega-Martínez; Efigenia Montalvo-González; José Martín Ruvalcaba-Gómez; Napoleón González-Silva; Luis Miguel Anaya-Esparza (Crops)
Maize plays a crucial role in global nutrition and food security, with Mexico making a significant contribution through its diverse native corn genotypes. However, research on flours derived from these native maize genotypes remains limited, hindering their potential applications in food manufacturing. This study aimed to determine the nutritional, physicochemical, techno-functional, structural, and antioxidant properties of corn kernel flours from nine native Mexican maize accessions cultivated in the highlands of Jalisco. Enough cobs for each maize accession were randomly selected to yield 1000 g of corn kernels. Data analysis was conducted by analysis of variance and Kruskal–Wallis tests (α = 0.05). Moreover, Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) were performed. Native corn kernel flour (NCKF) demonstrated higher protein and fat content compared to white hybrid corn flour (WHF). While both flours showed similar pH, titratable acidity, and water activity levels, NCKF exhibited higher total soluble solids. Additionally, NCKF showed superior techno-functional properties, including water solubility, water absorption index, swelling power, emulsifying capacity, and foaming capacity, while its oil absorption index was comparable to that of WHF. Moreover, NCKF contained higher levels of bioactive compounds, such as soluble phenols, condensed tannins, flavonoids, anthocyanins, and carotenoids, along with enhanced antioxidant properties, as measured by FRAP, DPPH, and ABTS assays. FTIR analysis revealed that all NCKF samples exhibited patterns similar to those of WHF with differences in transmittance intensities. Notably, spectral differences were identified by PCA, while HCA demonstrated that corn flours exhibited similitudes and differences among them, which can be categorized into four groups based on their nutritional, physicochemical, and technological–functional properties, as well as antioxidant compound contents. Overall, the evaluated corn flours displayed nutritional, physicochemical, techno-functional, and antioxidant properties for the potential development of functional or nutraceutical food and beverage products.